Evaluating the Surgical Outcomes of Free Flap Repair in Patients with Carcinoma of the Head and Neck - Fahim Ullah, Irfan Ishaq, Asadullah Awan, Masroor Ahmad Baloch, Majid Hussain, Athar Adnan Uppal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This research examined the risk factors for complications and the efficacy of free flap repair in early and recurrent head and neck cancer patients. Methods: A retrospective study of 160 head and neck cancer patients was conducted at different Hospitals of Pakistan. Free flap repair was performed on male and female primary and recurring cancer patients. After informed written agreement, detailed demographic information regarding enrolled cases was recorded. Group A had 80 recurrent cancer patients and group B had 80 primary cancer patients. Outcomes were compared. Results: In both groups, tumor stage 4 was the most common. The most common causes found in all cases were smoking, betel nut, and drinking. As far as flap types, the two most prevalent in both groups are anterior medial thigh (AMT) and anterior lateral thigh (ALT). In the initial tumors group, we observed 76 cases (95% success rate) with free flap repair, compared to 70 cases (87.5%) in the recurrent cancers group (p value <0.004). Concerning problems that arose after surgery, there was no discernible difference between the two groups. Conclusion: The results of this study indicate that the recurrent group had a higher failure rate for free flap reconstruction when compared to the primary group. However, it is possible that these differing patient characteristics are to blame for this outcome. Keywords: Surgical Outcomes, Free Flap Repair, Carcinoma, Head and Neck